The tech entrepreneur's survival guide : how to bootstrap your startup, lead through tough times, and cash in for success - Schoner, Bernd (McGraw Hill-Ascent Audio, 2014)
Most technology startups never make it to the funding stage, and only a small percentage of those that are venture-backed generate a positive return for their investors. An even smaller number of startup founders enjoy a truly prosperous exit. Bernd Schoner cofounded his tech startup during the dot-com bust, navigated it through market crises and internal turmoil, brought it through the global financial meltdown intact, and eventually sold it to a multibillion-dollar, multinational public technology company. In The Tech Entrepreneur's Survival Guide, Bernd shares what he learned and what he wished he knew at the time. He explains the major phases in a technology company's life cycle, helping entrepreneurs avoid common pitfalls and survive crises when they strike. He guides readers from the initial bootstrapping process through venture-capital financing and provides valuable advice on how to sell a technology company profitably--even in a challenging economic environment. Every chapter presents solutions to realworld issues that could otherwise have fatal consequences for a tech venture. Aspiring tech entrepreneurs will learn to: Set up shop: build the team, assemble necessary startup assets (including technology and intellectual property), get legal and financial affairs in order Secure capital: ask for money, nail the term sheet, ask for more money Get out: know when to sell, who to sell to, and how to make it a happy exit for all stakeholders, including the employees Written with deep insight, refreshing candor, and a dash of humor, this comprehensive guide to the often harsh realities of startup life is indispensable for entrepreneurs at any stage. PRAISE FOR THE TECH ENTREPRENEUR'S SURVIVAL GUIDE: "A genuine narrative from the field, with battle scars and self-reflection. Reading this book will help you avoid many pitfalls."--Nicholas Negroponte, professor at the Massachusetts Institute of Technology Media Lab "There's a lot of great insights and practical advice for the entrepreneur in this book, stuff you normally won't read or hear unless you buy some hard-bitten company founder a few drinks. If you are launching a technology startup, reading this book is the thing you should do first." -- Mark Roberti, founder and editor in chief of RFID Journal "I wish I had read Bernd's book when we founded The Echo Nest. Bernd touches on all the major issues in the initial formation stages of a tech company and many of the problems that come up when the company matures. If you are thinking of founding your own tech startup, read this book first." -- Tristan Jehan, cofounder of The Echo Nest "A visceral, behind-the-scenes guide to technology entrepreneurship. Bernd tells it like it is and presents a universe of solutions to tricky startup situations that can significantly improve the odds of success. Indispensable." -- Larry Begley, cofounder and managing director at .406 Ventures "The best-laid business plans never survive contact with reality. Bernd has provided a comprehensive guide to anticipating the unexpected in the life of a startup." -- Neil Gershenfeld, professor and director of the Massachusetts Institute of Technology Center for Bits and Atoms